2013
DOI: 10.3390/ijms14034762
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropins Activate Oncogenic Pathways to Enhance Proliferation in Normal Mouse Ovarian Surface Epithelium

Abstract: Ovarian cancer is the most lethal gynecological malignancy affecting American women. The gonadotropins, follicle stimulating hormone (FSH) and luteinizing hormone (LH), have been implicated as growth factors in ovarian cancer. In the present study, pathways activated by FSH and LH in normal ovarian surface epithelium (OSE) grown in their microenvironment were investigated. Gonadotropins increased proliferation in both three-dimensional (3D) ovarian organ culture and in a two-dimensional (2D) normal mouse cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Various signaling pathways have been implicated in gonadotropin-induced proliferation, invasion, and metastasis formation in ovarian cancer, such as the RAS/RAF/ MAPK/ERK (Pilarski et al 2012, Hilliard et al 2013, Smolle et al 2013, PI3K/PTEN/AKT/mTOR (Cancer Genome Atlas Research Network 2011, Huang et al 2011, Yamamoto et al 2011, 2012, Carden et al 2012, Abe et al 2013, Dobbin & Landen 2013, and Wnt/ b-catenin signaling pathways (Bodnar et al 2014, Ford et al 2014, Qi et al 2014. Gonadotropin (FSH and LH) receptors share various downstream signaling pathways, including PI3K and MAPK, and consequently, the potential crosstalk between gonadotropins and molecular pathway signaling is of great interest in exploring targeted cancer therapies.…”
Section: Treatments Targeting Downstream Results Of Endocrine Influencesmentioning
confidence: 99%
“…Various signaling pathways have been implicated in gonadotropin-induced proliferation, invasion, and metastasis formation in ovarian cancer, such as the RAS/RAF/ MAPK/ERK (Pilarski et al 2012, Hilliard et al 2013, Smolle et al 2013, PI3K/PTEN/AKT/mTOR (Cancer Genome Atlas Research Network 2011, Huang et al 2011, Yamamoto et al 2011, 2012, Carden et al 2012, Abe et al 2013, Dobbin & Landen 2013, and Wnt/ b-catenin signaling pathways (Bodnar et al 2014, Ford et al 2014, Qi et al 2014. Gonadotropin (FSH and LH) receptors share various downstream signaling pathways, including PI3K and MAPK, and consequently, the potential crosstalk between gonadotropins and molecular pathway signaling is of great interest in exploring targeted cancer therapies.…”
Section: Treatments Targeting Downstream Results Of Endocrine Influencesmentioning
confidence: 99%
“…Proliferation was measured using sulforhodamine B (SRB) colorimetric assay and analysis was completed using a Biotek Synergy 2 microplate reader as described previously(15, 51). …”
Section: Methodsmentioning
confidence: 99%
“…The potential role of FSH-FSH3 in stem cells with respect to ovarian biology was recently reviewed. 34 Similarly Hillard et al 63 recently reported that FSH increases mouse OSE proliferation through activation of oncogenic pathways in surface epithelial cells. It is likely that in women with POF and high levels of FSH, stem cells may undergo proliferation and initial differentiation.…”
Section: Differentiation Potential Of Vsels That Survive Chemotherapymentioning
confidence: 99%
“…Increase in proliferation of OSE in response to FSH or FSH analogs have been shown earlier both in vivo and in vitro. 31,35,[63][64][65][66] Patel et al 31 reported that the sheep ovarian stem cells express FSH receptors and undergo proliferation and clonal expansion in response to FSH via a novel FSHR transcript R3. The potential role of FSH-FSH3 in stem cells with respect to ovarian biology was recently reviewed.…”
Section: Differentiation Potential Of Vsels That Survive Chemotherapymentioning
confidence: 99%